STRATEGI KONTEN INSTAGRAM @BELOVASKINOFFICIAL DALAM MENINGKATKAN PENJUALAN PRODUK BELOVA - Kurnia Sari, Kristiana; Hindra, Nurnawati; Muadz, Muadz (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
ABSTRACT This study aims to analyze the Instagram content strategy of @belovaskinofficial in increasing sales of Belova skincare products during the period of July–December 2024. Using a descriptive qualitative research method, this study examines how the implemented content strategy attracts attention (Attention), builds interest (Interest), creates desire (Desire), and drives purchasing actions (Action) based on the AIDA model. Data were collected through interviews with the clinic owner, Instagram account manager, and Belova customers, as well as by analyzing engagement and sales data. The findings indicate that the applied content strategy successfully increased engagement but has not been fully effective in converting engagement into sales. Content featuring engaging visuals, storytelling, and clear call-to-action elements tends to be more effective in encouraging audience interaction. However, challenges such as slow admin responses and a lack of content variation remain obstacles in optimizing marketing effectiveness. This study recommends improving content quality and variation, optimizing call-to-action strategies, and enhancing audience interaction to increase the effectiveness of digital marketing strategies. Keywords: Content strategy, Instagram, Digital Marketing, AIDA Theory, Engagement